Employees' perceptions of corporate social responsibility and the relationship with organizational commitment and intention to stay in a telecommunications company - Ndjama, J. D. Ngo (My University, 2015)
The purpose of this study is to investigate the perceptions of employees of their organisation’s CSR activities and their effects on employees’ organisational commitment and intentions to stay. This study advocates that the way employees perceive their organisation’s CSR practices influences the types of attachment they have towards their organisation and reinforces their intentions to stay in their current organisation. The fact that employees play a central role in the realisation of an organisation’s goals makes it critical for any organisation to have employees who are willing to go beyond what is required of them and who are willing to stay in the organisation at least until the completion of their duties or contracts. In this study, a quantitative research paradigm and a descriptive research method were used to investigate a sample size of 350 employees working in one of the telecommunication organisations in Cameroon. In order to minimise the study bias, simple random sampling was used to ensure that the sample accurately reflects the larger population (N=670). Data was collected with the aid of a structured questionnaire and the results of the correlation analysis revealed that all four CSR dimensions are significantly and positively related to organisational commitment variables as well as to employees’ intentions to stay. CSR also showed strong predictive relationships with the various facets of organisational commitment. Organisational commitment in turn also showed strong predictive relationships with intention to stay within an organisation. Findings and recommendations of this study are important to employers as it provides crucial information regarding the types of activities organisations could engage in, and for employees to consider them as socially responsible. Such involvement in CSR activities can improve employees’ organisational commitment and reinforce their intentions to stay in their current organisation.
M. Tech. (Human Resource, Faculty of Management Sciences), Vaal University of Technology
Keywords: Corporate social responsibility; Employees organisational commitment; 658.408; Social responsibility of business.; Employees -- Attitudes.; Organizational commitment.; Organizational effectiveness -- South Africa.